2021
DOI: 10.1016/j.jvsv.2021.06.003
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Finding of Vein Thrombosis: Can IMPROVE and IMPROVEDD Scores Predict COVID-19 Outcomes?

Abstract: High rates of both venous and arterial thromboembolic events were observed early during the global COVID-19 pandemic, with severity of illness and need for intensive care unit admission correlating with increased thrombotic risk.Study Summary: This paper is a review of several observational studies that document the relatively high rates of thrombosis seen in hospitalized patients with COVID-19. Overall, the aggregate data demonstrate that the rates of arterial and venous thrombotic complications in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 0 publications
0
15
0
3
Order By: Relevance
“…To better assess the individual patients' risk for developing a thrombotic complication, we calculated the IMPROVE risk scores for all the patients. Since D-dimer levels were not routinely measured during the hospitalization, we calculated the IMPROVE and not IMPROVE-DD score [17,36,37]. However, we did not observe a clear association between a high IMPROVE score and the thromboembolic complication rates in our cohort.…”
Section: Discussionmentioning
confidence: 76%
“…To better assess the individual patients' risk for developing a thrombotic complication, we calculated the IMPROVE risk scores for all the patients. Since D-dimer levels were not routinely measured during the hospitalization, we calculated the IMPROVE and not IMPROVE-DD score [17,36,37]. However, we did not observe a clear association between a high IMPROVE score and the thromboembolic complication rates in our cohort.…”
Section: Discussionmentioning
confidence: 76%
“…One previous report by Greco et al 8 , showed that the IMPROVE score was not an independent predictor of the need for intensification of treatment; however, it was a risk factor for mortality. The unexplained contradiction in the results of Greco et al, might be due to the retrospective design, the small sample (51 patients), and the lack of evaluation of the severity of illness in the included patients.…”
Section: Discussionmentioning
confidence: 87%
“…The IMPROVE score was then validated showing good ability to risk-stratify acutely ill medical patients for VTE 6 and Similar findings had been reported in hospitalized patients with COVID-19 7 . In a retrospective analysis, high IMPROVE score was reported to be an independent predictor for 30-days mortality in patients with COVID-19 with undifferentiated severity 8 . To the best of our knowledge, there is no reports of prospectively evaluating the ability of IMPROVE and IMPROVE-DD score to predict outcomes in patients with severe COVID-19.…”
Section: Introductionmentioning
confidence: 97%
“…The IMPROVE score, for instance, has been explored in this setting where it predicts poor survival, while no data were reported regarding thrombosis. 8 With the aim of building up a score to predict thrombosis, we performed a multicenter observational study in a cohort of patients affected by SARS-CoV-2, in whom the occurrence of intrahospital thrombotic events was monitored.…”
Section: Introductionmentioning
confidence: 99%